Autonomy and participative processes in emotional education - Caetano, Ana Paula; Sobral, Catarina (European Public & Social Innovation Review, 2024)
Introduction: This paper presents a research about emotional education, with the purpose to identify and reflect on the introduction of changes in the educational process, to analyze the perspective of students about participative and autonomous processes, as well as the tensions and difficulties experienced. Methodology: A collaborative self-study project was conducted by two teachers of a graduate course of Teacher and Training during two school years affected by pandemic. It analyzes twenty six students’ portfolios and theirs written reflections on the educational processes and learning. Results: Participatory and autonomy processes undertook new formats and were boosted and developed in these exceptional circumstances. Students valued the building of a personal learning project, centered on their own goals for development and in conjunction with a class collective project. Several challenges and tensions arose, such as an immense flow of asynchronous interactions between teachers and students, very demanding for all, and inequalities in the conditions of access and use of the technologies. Conclusions: It is important to reinforce the emotional education research field exploring and problematizing the experiential and critical dimensions of emotional learning. That requires constant search for a creative integration of competence and critical approaches.